A 1.5 Ma Marine Record of Volcanic Activity and Associated Landslides Offshore Martinique (Lesser Antilles): Sites U1397 and U1399 of IODP 340 Expedition - Villemant, Benoît; Le Friant, Anne; Caron, Benoît; Del Manzo, Giulia; Lafuerza, Sara; Emmanuel, Laurent; Ishizuka, Osamu; Guyard, Hervé; Labourdette, Nathalie; Michel, Agnès; Hidalgo, Samia (Frontiers in Earth Science, 2022)
Holes U1397A and U1399A drilled during IODP Expedition 340, provide a 1.5 Ma record of the volcanic history of Martinique island. The reconstituted chronostratigraphy of hemipelagic sediments using 14C dating and δ18O patterns and the identification of tephra and volcaniclastic turbidites and of tracers of mass-wasting events (debris avalanche and debrite, duplication and deformation of pre-existing sediments) lead us to propose a new volcanic history that strongly modifies the previous models derived from on-land investigations. The top 50 m of core U1397A provides a continuous high resolution sedimentation record over the last ~130 ky. The sedimentation record deeper than 50 m and of the whole core U1399A are discontinuous because of the numerous sliding and deformation events triggered by flank collapses. Three main volcanic activity periods of decreasing production rates are recognized at Mt Pelée since ~190 ka: the ‘Old Pelée’ until 50 ka, the ‘Grand Rivière’ (20-50 ka) with the emission of mafic andesite together with silicic andesite characteristic of the whole activity period, and ‘Recent Pelée’ (20 ka – present day). At ~115 ka occurred a major flank collapse (‘Le Prêcheur’) that produced a debris avalanche and a submarine landslide that affected sea-floor sediments by erosion and deformation up to ~70 km from the shore. The Pitons du Carbet were active from 1.2 Ma to 260 ka, with, on average, a lower depostion rate of tephra falls than for Mt Pelée. It is also characterised by large flank collapses at a mean rate of 1 event every 100 ky, that produced debrite deposits and induced deformation in the related submarine landslides. Our data show that correlations between the timing of large landslides or emissions of more mafic magmas and rapid sea level rise or lowstands suggested by previous studies are not systematic. The combination of different factors is needed to trigger mass wasting or modifications of magma compositions. The reconstituted chronostratigraphy of cores U1397A and U1399A provides the framework necessary for further studies of the magma petrology, production rates and timing of the mechanisms triggering flank collapses and related submarine landslides of Mt Pelée and Pitons du Carbet.